Endobronchial valves for emphysema: an individual patient-level reanalysis of randomised controlled trials. Issue 1 (2nd November 2017) - Klooster, Karin; Slebos, Dirk-Jan; Zoumot, Zaid; Davey, Claire; Shah, Pallav L; Hopkinson, Nicholas S
Abstract : Introduction: Endobronchial valve placement has potential as a treatment for patients with chronic obstructive pulmonary disease (COPD). However, a robust evidence base will be needed to convince commissioners of healthcare that it is a high-value treatment. We sought to develop the evidence base by performing an individual patient-level analysis of randomised controlled trials in people with heterogeneous emphysema and an absence of collateral ventilation. Methods: A literature search (PROSPERO register CRD42016048127) identified two trials meeting these criteria, the BelieVeR-HIFi and STELVIO studies. Anonymised individual patient data were obtained from investigators and analysed. The primary outcome measure was a comparison of change in forced expiratory volume in 1 s (FEV1 ) from baseline between the treatment and control groups. Secondary end points were change from baseline in 6 min walk distance (6MWD), Medical Research Council dyspnoea score and St George's Respiratory Questionnaire (SGRQ). Results: 114 individuals were treated with 3-month to 6-month follow-up data available for 101 individuals. FEV1 improved by 23.1 (±28.3)% in patients treated with valves with a mean (95% CI) difference in response between groups of 17.8 (26.5, 9.2)% (p<0.0001). Relative to controls valve placement was associated with a fall in residual volume of 0.64 (0.43, 0.86) L (p<0.0001), a 9.5 (3.5, 15.6) unit fall in SGRQ (p=0.0022) and a 64.2 (94.0, 34.5) m increase in 6MWD. There were three deaths in the treatment arm and the pneumothorax rate was 15%. Conclusions: These data strengthen the evidence that endobronchial valve treatment can produce clinically meaningful improvements in appropriately selected COPD patients.